(untitled) - Miwa, Yoshiro (New York, 1996)
The great successes of the Japanese economy have often been attributed to differences in the Japanese economic system. Employing an exhaustive investigation of the roles of the government and banks, firms and networks, and workers and managers, Yoshiro Miwa illustrates that the standard principles of economics explain the dominant patterns of Japanese economic phenomena. Debunking many long-held myths, Miwa deftly propels readers to a fuller, more accurate understanding of the Japanese economy.
Keywords: Quản trị công nghiệp,Industrial management; Nhật Bản,Japan